Environmental remediation and restoration of contaminated nuclear and NORM sites - Velzen, Leo van (Cambridge, UK : Woodhead Publishing, an imprint of Elsevier, 2015)
Nuclear sites become contaminated with radionuclides due to accidents and activities carried out without due consideration for the environment. Naturally-occurring radioactive materials (NORM) released by industrial processes such as coal power production and fertilizer manufacture may also require clean-up. Environmental remediation and restoration aim to reduce exposure to radiation from contaminated soil or groundwater. This book provides a comprehensive overview of this area. Part 1 provides an introduction to the different types of contaminated site and their characteristics. Part 2 addre.
6 -- Modelling of radionuclide distribution in contaminated nuclear and NORM sites
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Nuclear energy -- Environmental aspects; Nuclear facilities -- Environmental aspects; Nuclear power plants -- Environmental aspects; Recreation areas -- Environmental aspects; BUSINESS & ECONOMICS / Real Estate / General; Nuclear energy -- Environmental aspects; Nuclear facilities -- Environmental aspects; Nuclear power plants -- Environmental aspects; Recreation areas -- Environmental aspects; Nuclear energy -- Environmental aspects; Nuclear facilities -- Environmental aspects; Nuclear power plants -- Environmental aspects; Recreation areas -- Environmental aspects; Electronic books; Electronic books; Electronic books